Loss of Protocadherin‐12 Leads to Diencephalic‐Mesencephalic Junction Dysplasia Syndrome. Issue 5 (4th October 2018) - Guemez‐Gamboa, Alicia; Çağlayan, Ahmet Okay; Stanley, Valentina; Gregor, Anne; Zaki, Maha S.; Saleem, Sahar N.; Musaev, Damir; McEvoy‐Venneri, Jennifer; Belandres, Denice; Akizu, Naiara; Silhavy, Jennifer L.; Schroth, Jana; et al.
Abstract : Objective: To identify causes of the autosomal‐recessive malformation, diencephalic‐mesencephalic junction dysplasia (DMJD) syndrome. Methods: Eight families with DMJD were studied by whole‐exome or targeted sequencing, with detailed clinical and radiological characterization. Patient‐derived induced pluripotent stem cells were derived into neural precursor and endothelial cells to study gene expression. Results: All patients showed biallelic mutations in the nonclustered protocadherin‐12 ( PCDH12 ) gene. The characteristic clinical presentation included progressive microcephaly, craniofacial dysmorphism, psychomotor disability, epilepsy, and axial hypotonia with variable appendicular spasticity. Brain imaging showed brainstem malformations and with frequent thinned corpus callosum with punctate brain calcifications, reflecting expression of PCDH12 in neural and endothelial cells. These cells showed lack of PCDH12 expression and impaired neurite outgrowth. Interpretation: DMJD patients have biallelic mutations in PCDH12 and lack of protein expression. These patients present with characteristic microcephaly and abnormalities of white matter tracts. Such pathogenic variants predict a poor outcome as a result of brainstem malformation and evidence of white matter tract defects, and should be added to the phenotypic spectrum associated with PCDH12 ‐related conditions. Ann Neurol 2018;84:638–647